Testing the J-curve phenomenon in Nigeria: An ARDL bounds testing approach - Sani Bawa; Rabia Muhammad Abdul; Zainab Sani; Mohammed Dauda (West African Journal of Monetary and Economic Integration, 2018)
This study examined the short-run and long-run effects of real exchange rate changes on the Nigeria's trade balance. The paper employed both linear and non-linear ARDL bounds testing approach to cointegration to test for the J-curve phenomenon in Nigeria using quarterly data spanning the period 1994 to 2018. Empirical results from the analysis revealed that real depreciation would lead to improvements in Nigeria's trade balance in the long-run. It also indicated that growth in foreign income tend to worsen the trade balance, while growth in domestic income improved the Nigeria's trade balance. In the short-run, however, our findings revealed that the J-curve phenomenon does not hold in Nigeria. The non-linear model result further provided additional evidence that the impact of real exchange rate changes on trade balance in Nigeria is asymmetric, as real depreciation played a significant role in influencing Nigeria's trade balance, while real appreciation does not have an impact. The study recommends a moderation in imports through an expansion in domestic production and the need to encourage non-oil exports in the country.
Keywords: C22; F14; F31; 330; Real Exchange Rate; Trade Balance; J-Curve; Depreciation